te000873: Le politicien : Je suis là ! - Deltour, Louis
"copyright: Deltour André, Deltour PhillippeZie ook: sch000226Zie ook: gou000374Zie ook: gou000375Zie ook: te000597Zie ook: te000875Zie ook: te000876Zie ook: te001971 FULL TEXT AVAILABLE AT AMSAB-ISH"